Consumer Preferences on Sago (Metrixylon Sp) Burger Modification: Analysis of Organoleptic Characteristics and Recipe Standardization - Mahyiddin, Zuraini; Hamid, Yuli Heirina; Indani, Indani; Faudiah, Nurul; Mizan, Akbar (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2024)
Sago palm, a natural product sourced from Simeulue Island, where the majority of the population engages in farming and fishing, is facing a decline in the production of sago flour. To address this issue, the author sought to incorporate sago flour (Metroxylon Sp) into the creation of burger buns, dubbed